How do we measure corporate social responsibility of Islamic banks through their business processes and oriented outcomes? - Rajeh, Abdullah Ali Alamer (Econjournals, 2015)
There are some academic efforts that have tried to measure corporate social responsibility (CSR) in Islamic banks (IBs) practices. But there is very lack in measuring the CSR of IBs through their operations not through their oriented outcomes. This article has suggested Musharakah and equity as new items to fill the important gap in measuring field of IBs’ CSR. In this work, the Musharakah is social and economic tool in IB finance and it is for the customers. Whilst the equity is a type of investments in IBs, in which the bank is as shareholder in other business organizations. It is coming from the deeper understanding of Shari’ah principles (Maqasid Shariah) in Islamic business world. With both cases (Musharakah with customers or equity with investors) IBs will share other in loss and profit and they are more far from Riba (interest rate) as in conditional banks. Not enough that IBs are undergo for Islamic law (Fiqhi) to reach the best level of CSR but they should have investments and financing that based on broad utility for the society. That is not mean that oriented-outcome side is not important of the IB’s CSR